Growth Phase, Oxygen, Temperature, and Starvation Affect the Development of Viable but Non-culturable State of Vibrio cholerae - Wu, Bin; Liang, Weili; Kan, Biao (Frontiers in Microbiology, 2016)
Abstract Vibrio cholerae can enter into a viable but non-culturable (VBNC) state in order to survive in unfavourable environments. In this study, we studied the roles of five physicochemical and microbiological factors or states, namely, different strains, growth phases, oxygen, temperature, and starvation, on the development of VBNC of V. cholerae in artificial sea water (ASW). Different strains of the organism, the growth phase, and oxygen levels affected the progress of VBNC development. It was found that the VBNC state was induced faster in V. cholerae serogroup O1 classical biotype strain O395 than in O1 El Tor biotype strains C6706 and N16961. When cells in different growth phases were used for VBNC induction, stationary-phase cells lost their culturability more quickly than exponential-phase cells, while induction of a totally non-culturable state took longer to achieve for stationary-phase cells in all three strains, suggesting that heterogeneity of cells should be considered. Aeration strongly accelerated the loss of culturability. During the development of the VBNC state, the culturable cell count under aeration conditions was almost 106-fold lower than under oxygen-limited conditions for all three strains. The other two factors, temperature and nutrients-rich environment, may prevent the induction of VBNC cells. At 22°C or 37°C in ASW, most of the cells rapidly died and the culturable cell count reduced from about 108 CFU/mL to 106–105 CFU/mL. The total cell counts showed that cells that lost viability were decomposed, and the viable cell counts were the same as culturable cell counts, indicating that the cells did not reach the VBNC state. VBNC state development was blocked when ASW was supplied with Luria-Bertani broth (LB), but it was not affected in ASW with M9, suggesting that specific nutrients in LB may prevent the development of VBNC state. These results revealed that the five factors evaluated in this study had different roles during the progress of VBNC induction. Changing a single factor could influence and even block the development of the VBNC state. These findings provide new insight to help design further studies to better understand the mechanisms which trigger the development and regulation of the VBNC